Antinuclear antibodies produced in HLA-DR transgenic humanized mice developed chronic graft-versus-host disease. Issue 11 (November 2021) - Tsuzuki, Hiroshi; Nagatsuka, Yasuko; Iwata, Mitsuhiro; Kitamura, Noboru; Nagasawa, Yosuke; Matsumoto, Taro; Ito, Ryoji; Takahashi, Takeshi; Ito, Mamoru; Nakamura, Hideki; Takei, Masami
Abstract: Background: Chronic graft versus host disease (GVHD) has been reported in humanized mice after the implantation of human hematopoietic stem cells (hu-HSC). As such, humanized mice have been applied to a mouse model of chronic GVHD; however, B-cell activation and autoantibody production did not occur, and the clinical features of chronic GVHD were not sufficiently reproduced. The purpose of this study was to establish an improved humanized mouse model with chronic GVHD using HLA-DR transgenic NOD/Shi-scid, IL-2RγKO (NOG) mice. Methods: CD34-positive cells were isolated from blood extracted from HLA-DRB1∗0405-positive umbilical cords using magnetic cell isolation. Then these were transplanted into NOG-Iab KO, HLA-DR 0405 Tg mice aged 8–16 weeks. GVHD symptoms were observed 26 weeks after transplantation. Histological findings of the skin, lung, liver, and spleen were compared with those of non-humanized mice. Antinuclear antibodies (ANA) were measured by indirect immunofluorescence using sera isolated 26 weeks after transplantation. Results: Although GVHD symptoms were not observed in humanized (hu-HSC) NOG-Iab KO, HLA-DR 0405 Tg mice during the observation period, histological findings of human T-cell infiltration were observed in the skin, liver, and lung, suggesting that GVDH was present; human tingible body macrophages or clusters of BCL-6-positive human B-cells were observed in the spleen. Furthermore, human IgG ANA with peripheral or homogeneous staining patterns were also detected in the sera. Conclusion: Hu-HSC NOG-Iab KO, HLA-DR 0405 Tg mice differed from conventional models in terms of B-cell activation and ANA production. This study is the first to report on B-cell activation and autoantibody production in humanized mice with chronic GVHD, suggesting that hu-HSC NOG-Iab KO, HLA-DR 0405 Tg mice could be applied to a new humanized mouse model of chronic GVHD. Abstract : Chronic GVHD, HLA-DR transgenic humanized mouse, Autoantibody, Antinuclear antibody.